The role of bacterial and viral infection in exacerbation of bronchiectasis: a prospective study. Issue 1 (October 2019) - Chen, Chun-Lan; Huang, Yan; Yuan, Jing-Jing; Li, Hui-Min; Han, Xiao-Rong; Martinez-Garcia, Miguel Angel; Chen, Rong-Chang; Guan, Wei-Jie; Zhong, Nan-Shan
Abstract: Background: Exacerbations are crucial events in the progression of bronchiectasis. Previous studies have documented associations between viral or bacterial infection and bronchiectasis exacerbations, but assays for viral or bacterial infection were conducted separately. No study has yet revealed an association between bacteria and viruses in bronchiectasis exacerbations. Moreover, the clinical correlates of bacterial with or without viral detections are unclear. We sought to explore associations between bacterial infection, viral infection and co-infection, and exacerbation of bronchiectasis. Methods: In this prospective cohort study, we enrolled 108 patients from the outpatient clinics of The First Affiliated Hospital of Guangzhou Medical University (Guangzhou, China). The participants were followed up every 3–6 months and at exacerbation episodes, between March, 2017, and November, 2018. Each sputum sample was split into two for detection of bacteria (routine culture) and viruses (quantitative PCR). Clinical characteristics were assessed during exacerbation episodes. Findings: The median exacerbation rate was 2·0 (interquartile range 1·0–2·5) per patient per year. Viral infection was correlated with significantly higher risks of exacerbation (29% [22 of 76] of exacerbation episodes; OR 3·28, 95% CI 1·76–6·12) than non-viral infection. Similarly, new occurrence of bacterial infection was correlated with significantly higher risks of exacerbation (eg, Haemophilus influenza was associated with 11% [eight of 26] of exacerbation episodes; 2·52, 1·35–4·71) than no new occurrence of bacterial infection, and likewise co-infection (2·24, 1·11–4·55) than all of the other groups combined. A positive bacterial culture alone was not correlated with exacerbations (p>0·778). Although coryza seemed to be more common in viral exacerbation than in unexplained and new bacterial exacerbation (p=0·053), lower airway symptoms were more severe in new bacterial exacerbation (visual analogue scale for cough, p=0·030; sputum volume, p=0·006; sputum purulence, p=0·025). Airway interleukin-1β levels were consistently higher in new bacterial exacerbation than in unexplained and viral exacerbation (p=0·007). A significantly greater number of coryza was correlated with co-infection at exacerbation (p=0·019). However, co-infection did not differ from bacterial or viral infection alone in lower airway symptoms (p=0·063), lung function decline (forced expiratory volume in one second, p=0·278; forced vital capacity, p=0·230), and sputum cytokine levels (interleukin-1β, p=0·445; CXC motif chmokine-8, p=0·279; tumour necrosis factor-α, p=0·055; and interferon-γ, p=0·555). Interpretation: Viral infection, new occurrence of bacterial infection and co-infection are associated with exacerbation of bronchiectasis. The clinical characteristics of bronchiectasis exacerbation might inform clinicians of the possible underlying pathogens. Funding: This work was supported by the National Natural Science Foundation (no. 81870003 ), Pearl River S&T Nova Program of Guangzhou (no. 201710010097 ) and Guangdong Province Universities and Colleges Pearl River Scholar Funded Scheme 2017 (to W-JG), and the Impact and Mechanisms of Physical, Chemical and Biological Interventions on the Development and Outcome of Acute Lung Injury (no. 81490534, to N-SZ).